Biofilm forming Salmonella strains exhibit enhanced thermal resistance in wheat flour. (March 2017) - Villa-Rojas, Rossana; Zhu, Mei-Jun; Paul, Narayan C.; Gray, Peter; Xu, Jie; Shah, Devendra H.; Tang, Juming
Abstract: The biofilm lifestyle of bacteria confers a remarkably increased tolerance to antimicrobial interventions and environmental stresses, however little is known about influence of biofilms on thermal resistance of Salmonella in low-moisture foods. This study was aimed to assess the correlation between the ability of biofilm formation of Salmonella Enteritidis ( S. Enteritidis) strains and their capacity to survive desiccation and thermal treatment in wheat flour as a model for low-moisture food. The production of the biofilm in S. Enteritidis strains was analyzed qualitatively and quantitatively using calcoflour fluorescence, congo-red binding, pellicle formation and microtiter-plate test. Subsequently, three biofilm-forming and four non-forming S. Enteritidis strains were selected. Survival after desiccation was evaluated by population counts before and after equilibration for 4–5 days at 45% RH. Thermal resistance (D80 °C, 0.45 aw ) of S. Enteritidis in wheat flour was evaluated by fitting the thermal inactivation kinetic data with the first order kinetics model. The biofilm forming ability was not associated with resistance to desiccation. However, thermal resistance (D80 °C, 0.45 aw ) and pre-formed biofilm amount (OD492 nm ) showed a linear correlation (Spearmen correlation ρ = 0.8, p < 0.05), indicating more biofilm production confers more thermal resistance. Average thermal resistance (D80 °C, 0.45 aw ) was significantly (p < 0.05) higher among biofilm formers (14.1 ± 0.6 min) when compared with non-formers (6.0 ± 0.2 min). This study shows that the amount of biofilm produced by Salmonella on congo red-calcofluor media is linearly correlated with the thermal resistance of Salmonella in wheat flour. The findings reinforce the necessity of appropriate management in sanitation and biofilm removal in plants that process low-moisture foods. Highlights: Salmonella Enteritidis biofilm is not associated with short-time desiccation survival. Biofilm amount is positively correlated to S. Enteritidis thermal resistance. Salmonella biofilm increases its thermal resistance in a dry environment.